2013
DOI: 10.1155/2013/463401
|View full text |Cite
|
Sign up to set email alerts
|

Back Propagation Neural Network Model for Predicting the Performance of Immobilized Cell Biofilters Handling Gas-Phase Hydrogen Sulphide and Ammonia

Abstract: Lab scale studies were conducted to evaluate the performance of two simultaneously operated immobilized cell biofilters (ICBs) for removing hydrogen sulphide (H2S) and ammonia (NH3) from gas phase. The removal efficiencies (REs) of the biofilter treating H2S varied from 50 to 100% at inlet loading rates (ILRs) varying up to 13 g H2S/m3 ·h, while the NH3 biofilter showed REs ranging from 60 to 100% at ILRs varying between 0.5 and 5.5 g NH3/m3 ·h. An application of the back propagation neural network (BPNN) to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 38 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…The process of gender classification was carried out using BPNN with two types of parameter setting. The first one was the standard parameter setting based on previous researchers (Tsai & Lee, 2011;Rene et al, 2013) and the second parameter setting was an Automated Parameter Tuning as shown in Figure 3. Automated parameter tuning was based on the parameter optimization incorporating grid search algorithm and cross-validation which was carried out in the experiment.…”
Section: Optimized Back Propagation Neural Networkmentioning
confidence: 99%
“…The process of gender classification was carried out using BPNN with two types of parameter setting. The first one was the standard parameter setting based on previous researchers (Tsai & Lee, 2011;Rene et al, 2013) and the second parameter setting was an Automated Parameter Tuning as shown in Figure 3. Automated parameter tuning was based on the parameter optimization incorporating grid search algorithm and cross-validation which was carried out in the experiment.…”
Section: Optimized Back Propagation Neural Networkmentioning
confidence: 99%
“…In the modeling process, training data were analyzed and then the decision was made through output neurons when new input variables were put in [31]. In most of the ANN models, the backpropagation (BP) network was the commonly used solution in dealing with the nonlinear relationship between input variables and output variables by constantly adapting the connection weight value between neurons and the error threshold in each layer to make the output variables approximately towards the expected outcome [32][33][34][35][36]. The BP algorithm was based on error gradient descent (Figure 1), which was aimed at finding the minimum error by adjusting weights of connections between neurons in the direction of lowest error [37].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, the application of ANN in desulfurizing BF modeling has been few reported so far [13,[36][37][38], despite the wide use of the desulfurizing BFs. Therefore, this study was conducted to enrich this research gap.…”
Section: Introductionmentioning
confidence: 99%